2009
DOI: 10.1111/j.1600-0889.2009.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Solar dimming and brightening over Thessaloniki, Greece, and Beijing, China

Abstract: This work presents evidence that ultraviolet (UV)‐A solar irradiances show increasing trends at Thessaloniki, Greece, where air quality has been improving because of air pollution abatement strategies. In contrast, over Beijing, China, where air quality measures were taken later, solar brightening was delayed. It is shown that until the early 1990s, UV‐A irradiances over Thessaloniki show a downward trend of –0.5% yr−1, which reverses sign and becomes positive in the last decade (+0.8% yr−1). This brightening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 51 publications
5
16
0
Order By: Relevance
“…Both trends are found to be statistically significant at the 95% confidence level, underlying a significant increase in aerosol load over Hyderabad in the last 6 years, mainly attributed to the economic growth and industrialization, population growth, increased vehicular emissions and expansion of the city. This increasing trend is opposite to that observed in the AOD over Mediterranean [Papadimas et al, 2008] and Thessaloniki, Greece (decreasing rate of −4.5% yr −1 ), but it is in agreement with the increasing AOD trend (1.0% yr −1 ) over Beijing between 2000 and 2008 [Zerefos et al, 2009]. Such a large increase in AOD over an urban area with surrounding industrial activities may be a significant reason for the solar dimming over Hyderabad observed in the recent years, even under clear (without clouds) atmospheres (Figure 1c).…”
Section: Influence Of Aerosolssupporting
confidence: 59%
See 4 more Smart Citations
“…Both trends are found to be statistically significant at the 95% confidence level, underlying a significant increase in aerosol load over Hyderabad in the last 6 years, mainly attributed to the economic growth and industrialization, population growth, increased vehicular emissions and expansion of the city. This increasing trend is opposite to that observed in the AOD over Mediterranean [Papadimas et al, 2008] and Thessaloniki, Greece (decreasing rate of −4.5% yr −1 ), but it is in agreement with the increasing AOD trend (1.0% yr −1 ) over Beijing between 2000 and 2008 [Zerefos et al, 2009]. Such a large increase in AOD over an urban area with surrounding industrial activities may be a significant reason for the solar dimming over Hyderabad observed in the recent years, even under clear (without clouds) atmospheres (Figure 1c).…”
Section: Influence Of Aerosolssupporting
confidence: 59%
“…A recent study over China and Japan [Norris and Wild, 2009] has proved that the variations in cloudiness and cloud properties (optical depth, albedo) are most responsible for the changes in solar radiation reaching the ground. However, large decadal changes in solar radiation are not found only for all-sky conditions (including clouds), but also for cloudless atmospheres [e.g., Ohvril et al, 2009;Zerefos et al, 2009] indicative of anthropogenic contributions through changes in aerosol emissions governed by economic development.…”
Section: Influence Of Cloudsmentioning
confidence: 99%
See 3 more Smart Citations